Ara h 2 and Ara h 6 sensitization predicts peanut allergy in Mediterranean pediatric patients. Issue 7 (10th December 2014) - Agabriel, Chantal; Ghazouani, Ouafeh; Birnbaum, Joëlle; Liabeuf, Valérie; Porri, Françoise; Gouitaa, Marion; Cleach, Isabelle; Grob, Jean‐Jacques; Bongrand, Pierre; Sarles, Jacques; Vitte, Joana
Abstract Background Peanut allergy (PA) management was improved by the introduction of molecular allergology, but guidelines for Mediterranean patients are lacking. We aimed at evaluating peanut component‐resolved diagnosis as a diagnostic and prognostic tool in children from Southern France. Methods In 181 pediatric patients, PA diagnosis was founded on medical history, skin prick testing, serum‐specific IgE to Arachis hypogea extract and components, Pru p 4, and plant carbohydrates, and oral food challenge. Allergen microarray was also performed in 68 of these patients. Results In peanut‐allergic children (n = 117), IgE to Ara h 6 were most prevalent (64%), followed by Ara h 2 (63%), Ara h 1 (60%), and Ara h 9 (52%). Ara h 6 was the best predictor of PA. The second best predictor was the ratio of Ara h 2 IgE to peanut IgE (cutoff 0.113). Persistent childhood PA was associated with complex molecular profiles. Comparison of singleplex and microarray results showed poor concordance for Ara h 2 and Ara h 9. Conclusion Ara h 6 and Ara h 2 are the best predictors of PA at diagnosis in Mediterranean pediatric patients. Ara h 1, Ara h 8, and molecular complexity are associated with PA persistence.